IoT recycle management system to support green city initiatives - Ruwaida Ramly; Aznida Abu Bakar Sajak; Muhaira Rashid (Institute of Advanced Engineering and Science, 2019)
In July 2009, Government of Malaysia had launched Green Technology Policy as new initiatives from Malaysia to handle greenhouse effect issue and energy usage through application and green technologies development to reduce carbon footprint. This project, Internet of Things (IoT) Recycle Management System is an idea to help the government in gearing the nation towards this aim with a developed system or technology that support green environment. For this paper, the intended cities are Putrajaya and Cyberjaya areas since both of these cities are chosen as a pioneer for the Green City Initiatives by the Government. This Arduino based Internet of Things (IoT) project is an upcoming urban technology that transforms everyday current recycling system into an ecosystem that would enrich our lives and make it exciting to recycle things anywhere. Hence, encourages Malaysian to recycle their things regularly and make it as a normal routine. This project consists of the development of recycle waste bin that have sensor-based and a database with webpage system for client interface which be connected via Internet network. This project has a huge prospect to be implemented in the future, should there be a collaboration with Government entities and Non- Government entities as this effort needs huge support from all Malaysians in order to realize first class mentality transformation.